Порівняльний аналіз технологій OSDP та WIEGAND - Якимович, М. В. (ХНУРЕ, 2023)
The research described the comparative comparison of Open Supervised Device Protocol and Wiegand interface
Keywords: технологія OSDP; технологія WIEGAND